2020
DOI: 10.1111/famp.12544
|View full text |Cite
|
Sign up to set email alerts
|

My Brother’s Keeper? The Sibling Subsystem in the Context of Physical and Sexual Child Abuse

Abstract: The sibling subsystem is of central importance and a possible protective factor for children. Nevertheless, it remains surprisingly understudied and lacks any theoretical or conceptual framework. The current study explored the sibling subsystem in the context of child abuse (CA). Thorough thematic analysis was conducted on the narratives of 30 children referred to forensic interviews following suspected physical or sexual abuse by a parent. Aged 4–14, all had at least one sibling each and referred to this sibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…The literature on the experiences of those involved in sibling sexual relationships has been expanding in recent years (e.g., Katz & Tener, 2021) The resulting sample consisted of 20 adults (13 women and 7 men) from the Jewish Orthodox community in Israel, ranging in age from 20 to 68, who experienced sexual interaction with one or more of their siblings as children. Thirteen of the participants define themselves as Orthodox today and seven have left the religious world.…”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature on the experiences of those involved in sibling sexual relationships has been expanding in recent years (e.g., Katz & Tener, 2021) The resulting sample consisted of 20 adults (13 women and 7 men) from the Jewish Orthodox community in Israel, ranging in age from 20 to 68, who experienced sexual interaction with one or more of their siblings as children. Thirteen of the participants define themselves as Orthodox today and seven have left the religious world.…”
Section: The Current Studymentioning
confidence: 99%
“…The literature on the experiences of those involved in sibling sexual relationships has been expanding in recent years (e.g., Katz & Tener, 2021) but does not emphasize the role of religious culture in the phenomenon. The present study aims to fill this theoretical gap by obtaining the emic viewpoints of siblings involved in SSD within the Jewish Orthodox community in Israel.…”
Section: Introductionmentioning
confidence: 99%
“…These theories serve to explicate research findings on how siblings are negatively impacted, both in the short term and long term, by exposure to maltreatment of a family member, such as domestic violence or violence toward a sibling. For example, Teicher and Vitaliano (2011) reported that witnessing violence toward a sibling is associated with symptoms of depression, anxiety, somatization, anger‐hostility, dissociation, and “limbic irritability.” Few published papers have directly focused on the psychological impact of CSA on nonabused siblings and these have primarily focused on child siblings (Hill, 2003; Katz & Hamama, 2018; Schreier et al., 2017; Tener & Katz, 2021). Such papers have highlighted the psychological impact of CSA on nonabused siblings and the need to include these children in therapeutic responses to CSA.…”
Section: Child Sexual Abuse and Sibling Relationshipsmentioning
confidence: 99%
“…A substantial body of work over the past three decades has documented the negative influence of exposure to intimate partner violence (IPV) on children's adjustment (Carter et al., 2020). Unfortunately, much less is known about how exposure to IPV impacts children's sibling relationships (Katz & Tener, 2020). It has been widely demonstrated that siblings are important influences on children's social, emotional, and cognitive development (Kramer et al., 2019), as well as on their mental health and well‐being, particularly in contexts of adversity (Osher et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…First, as noted, past research has found these linkages in families without a history of IPV (Buist & Vermande, 2014). Second, these linkages may reflect the buffering or compensatory role siblings sometimes play under adverse circumstances (Katz & Tener, 2020). Therefore, the second goal of our investigation was to empirically explore if sibling warmth was significantly associated with prosocial behaviour between siblings exposed to IPV.…”
Section: Introductionmentioning
confidence: 99%